Telecommunication Economics: Selected Results of the COST Action IS0605 - Hadjiantonis, Antonis M. (Lecture Notes in Computer Science, 2012)
Computer Communication Networks; Communications Engineering, Networks; Computers and Society; Management of Computing and Information Systems